ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT APARAT PENGAWAS INTERN PEMERINTAH (Studi Empiris Pada Inspektorat Kota Semarang) (Students' Journal of Accounting and Banking, 2014)
This study aims to analyze empirically the influence of the independence, objectivity, competence, work experience, integrity, ethics audits and time pressure on audit quality in the Government Internal Control Apparatus ( APIP ) Inspektorat Semarang. The population in this study is the Internal Control Inspektorat officials Semarang. The samples used were 49 respondents, sampling is done by using purposive sampling method which has been followed as an auditor Training (Training Certification JFA). Primary data collection method used was a questionnaire method. Data were analyzed using multiple linear regression models. The results showed that the independence, objectivity, integrity and ethics audits positive and significant impact on audit quality. While competence, work experience is not significant and positive effect of time pressure is not a significant negative effect on audit quality.Keywords: Independence, objectivity, competence, work experience, integrity, ethics audits, time pressure, quality audits